H2O2/UV-C treatment of the commercially important aryl sulfonates H-, K-, J-acid and Para base: Assessment of photodegradation kinetics and products - Arslan-Alaton, Idil; Olmez-Hanci, Tugba; Gursoy, Betul Hande; Tureli, Gokce (Elsevier BV, 2009)
H2O2/UV-C treatment of four commercially important aryl sulfonates (naphthalene sulfonic acids H-acid, K-acid, J-acid and benzene sulfonic acid Para base) in aqueous solutions was investigated. Photodegradation kinetics was followed in terms of changes brought about in the parent compound concentration via high performance liquid chromatography, as well as abatement of the collective environmental parameters COD and TOC. The efficiency of H2O2/UV-C treatment was also evaluated by determining H2O2 consumption rates throughout the reactions whereas the formation of intermediates (photodegradation products) was traced by means of mass spectrometry. Our experimental findings indicated that especially trisulfonated K-acid was not very prone to photochemical degradation, closely followed by the other studied aryl sulfonates. The highest abatement rates (treatment efficiencies and reaction kinetics) were obtained for the relatively simpler structured Para base. Mass spectrometric analysis revealed that the early stages of H2O2/UV-C treatment followed a (.)OH-addition mechanism as mainly hydroxylated photodegradation products were qualitatively identified.
Keywords: Photolysis; Ultraviolet Rays; Benzenesulfonates; Hydrogen Peroxide; Hydrogen-Ion Concentration; Sulfuric Acid Esters; Kinetics; Naphthalenesulfonates; Naphthylamine; Environmental Pollutants; Organic Chemicals; Sulfonic Acids; Oxidation-Reduction